Analisis Efektivitas Metode SQ3R dalam Meningkatkan Pemahaman Bacaan - Emira Hayatina Ramadhan; Rian Dwiyanto; Mahmudah Fitriyah Z.A. (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2024)
This study aims to evaluate the effectiveness of the SQ3R (Survey, Question, Read, Recite, Review) method in improving reading comprehension, with an emphasis on analyzing the advantages, disadvantages, and factors affecting its application. The SQ3R method is applied to various types of texts, including textbooks, scientific articles, and literary literature. This research is a literature study, which focuses on analyzing and synthesizing relevant literature to evaluate the impact of SQ3R in a learning context. The results of the literature study will provide deep insights into the effectiveness of SQ3R in improving reading comprehension, as well as the potential advantages, disadvantages, and barriers that may be encountered. This research is expected to contribute to further understanding of the application of the SQ3R method in learning contexts and provide a foundation for future research.